2012
DOI: 10.5588/ijtld.12.0038
|View full text |Cite
|
Sign up to set email alerts
|

Screening outcomes from patients with suspected multidrug-resistant tuberculosis: lessons learned in the Philippines

Abstract: Resistance to INH+RMP is the most frequent resistance pattern among patients referred from DOTS clinics in the Philippines for suspected MDR-TB. Initial use of standard regimens based on national survey data and quick uptake of new rapid molecular resistance tests may be useful to reduce diagnostic delays and expedite treatment for drug-resistant TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…This was in concordance with the result of another study in Philippines that found MDR as the most frequent resistance pattern among TB patients (42). We found that 3 (3.2% of all patients, 9.3% of MDR patients and 20% of INH resistant cases) had KatG or InhA gene mutation and 9 (9.7% of all patients, 28% of MDR patients and 60% of INH resistant cases) exhibited mutation in both genes by Allele Specific PCR in this study.…”
Section: Discussionsupporting
confidence: 92%
“…This was in concordance with the result of another study in Philippines that found MDR as the most frequent resistance pattern among TB patients (42). We found that 3 (3.2% of all patients, 9.3% of MDR patients and 20% of INH resistant cases) had KatG or InhA gene mutation and 9 (9.7% of all patients, 28% of MDR patients and 60% of INH resistant cases) exhibited mutation in both genes by Allele Specific PCR in this study.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, DR and MDR TB cases had higher proportions changing or initiating treatment after DST results and higher favorable outcomes, similar to those described (44.0%–57.0%) by Yacobson [ 15 ] and Gler [ 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…Probably, physicians started anti-TB medication for suspected drug resistant TB before the results of susceptibility testing, due to previous delays experienced in the release of such results by phenotypic tests. Nevertheless, the median release time of DST results was 69.5 days, similar to (52–70 days) observed by Hannarah [ 10 ], Tukvadze et al [ 11 ] and Yadava et al [ 14 ] and lower than described (106–133 days) by Boheme et al [ 12 ], Shin et al [ 24 ], and Gler et al [ 25 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Application of rapid DST techniques, including providing finances and reagent supplies, may be useful to reduce diagnostic delays and expedite treatment for drug‐resistant TB, but the methods should be piloted before wide application . GeneXpert MTB/RIF, line probe assays and Genechip are being evaluated by China's National Reference Laboratory, but are yet to be incorporated into the current diagnostic algorithms.…”
Section: Discussionmentioning
confidence: 99%